PERCEIVED USEFULNESS WITHIN THE TECHNOLOGY ACCEPTANCE MODEL FRAMEWORK AND FINTECH ADOPTION: AN INTEGRATED REVIEW OF FINDINGS FROM DEVELOPING COUNTRIES - Araujo, Delia Iria Magno De; Nabir, Abdul Muhaemin; Jainuddin; Ranawati, Tri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze the role of perceived usefulness in influencing the adoption of financial technology (fintech) using the Technology Acceptance Model (TAM) framework, by integrating findings from literature reviews across various developing countries. As fintech implementation continues to expand as a tool for promoting financial inclusion, understanding the determinants of technology adoption becomes increasingly crucial, especially in countries with varying levels of technological penetration. This research adopts a systematic literature review method of scholarly articles published between 2019 and 2024 to identify patterns, trends, and contextual variables that mediate or moderate the influence of perceived usefulness on fintech adoption intentions and behaviors. The findings reveal that perceived usefulness is a primary determinant in the adoption of fintech in most developing countries. However, its influence is often mediated by external factors such as digital literacy levels, trust in the system, technological infrastructure, and national regulatory frameworks. These results offer theoretical contributions to the expansion of the TAM in cross-cultural contexts and practical implications for policymakers and fintech providers in designing more context-specific and locally responsive adoption strategies.